TESTING EARTHQUAKE PREDICTION METHODS: "THE WEST PACIFIC SHORT-TERM FORECAST OF EARTHQUAKES WITH MAGNITUDE MWHRV ≥ 5.8" - Kossobokov V.G. (My University, 2006)
Analyzing the tables and probability maps posted by Yan Y. Kagan and David D. Jackson in April 2002–September 2004 at http://scec.ess.ucla.edu/~ykagan/predictions_index.html and the catalog of earthquakes for the same period, the conclusion is drawn that the underlying method could be used for prediction of aftershocks, while it does not outscore random guessing when main shocks are considered.